Experimental and numerical analysis of the complex permittivity of open-cell ceramic foams. Issue 17 (1st December 2020) - Camacho Hernandez, Jesus Nain; Link, Guido; Soldatov, Sergey; Füssel, Alexander; Schubert, Markus; Hampel, Uwe
Abstract: Open-cell ceramic foams are promising materials in the field of microwave heating. They can be manufactured from susceptor materials and can, therefore, be used as selective heating elements. In this study, the complex permittivities of ceramic foam materials, including silicon-infiltrated silicon carbide (SiSiC), pressureless sintered silicon carbide (SSiC), silicate-bonded silicon carbide (SBSiC), and cordierite were determined. The dielectric properties of the foams were determined by the cavity perturbation technique using a TE104 WR340 waveguide resonator at 2.45 GHz. Samples were preheated in a tubular furnace, enabling temperature-dependent permittivity measurements up to 200 °C. The effective dielectric constant and effective loss factor were found to depend on the porosity and material composition of the foam. The SiSiC material had a higher effective dielectric constant than the SSiC and SBSiC ceramics. The effective dielectric constant of the foams showed a trend of gradual increase with increasing temperature. Some selected dielectric mixing relations were then applied to describe the effective permittivity of the foams and compare them with predictions from finite element simulations performed using the CST Studio Suite. The foam morphologies and simple block inclusions were used in the simulations.